NUCLIDE PREPARATION SYSTEM BASED ON HIGH-DENSITY ELECTRON LINEAR ACCELERATOR - HOR, Yuen Keung; HUANG, Yongsheng; CHEN, Ruan (2023)
A nuclide preparation system based on a high-density electron linear accelerator. The nuclide preparation system comprises a high-density electron accelerator module, a target making and shooting module, and a nuclear medicine purification and separation module, wherein the high-density electron accelerator module is used for generating a 39.8 MeV high-energy electron beam; the high-energy electron beam bombards the target making and shooting module, so as to generate a large amount of gamma rays γ with bremsstrahlung and secondary neutron beams with bremsstrahlung; and the gamma rays γ and the secondary neutron beams bombard a Mo sample target, which is arranged in the nuclear medicine purification and separation module, so as to generate 99Mo radioisotopes. An overall solution, by means of which 99Mo radioisotopes can be produced and prepared, is provided in the present invention, and by means of the solution, gamma rays γ having enough energy can be generated, such that 99Mo radioisotopes, which meet actua